2011
DOI: 10.1038/npp.2011.175
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nociceptin/Orphanin FQ Peptide Receptors Disrupts Visual but Not Auditory Sensorimotor Gating in BALB/cByJ Mice: Comparison to Dopamine Receptor Agonists

Abstract: Nociceptin/orphanin FQ (N/OFQ) peptide and its receptor (NOP receptor) have been implicated in a host of brain functions and diseases, but the contribution of this neuropeptide system to behavioral processes of relevance to psychosis has not been investigated. We examined the effect of the NOP receptor antagonists, Compound 24 and J-113397, and the synthetic agonist, Ro64-6198, on time function (2-2000 ms prepulse-pulse intervals) of acoustic (80 dB/10 ms prepulse) and visual (1000 Lux/20 ms prepulse) prepulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 74 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…During the acquisition session, Ro64-6198 increased the time spent exploring the object, an effect that seems to reflect a psychomotor stimulant rather than an anxiolytic-like action of this compound (Ces et al, 2012;Goeldner et al, 2008). Such increase in exploratory activity cannot account for the memory deficit.…”
Section: Discussionmentioning
confidence: 89%
“…During the acquisition session, Ro64-6198 increased the time spent exploring the object, an effect that seems to reflect a psychomotor stimulant rather than an anxiolytic-like action of this compound (Ces et al, 2012;Goeldner et al, 2008). Such increase in exploratory activity cannot account for the memory deficit.…”
Section: Discussionmentioning
confidence: 89%
“…The pattern of deficits obtained with visual PPI also argues against an impairment of the visual prepulse detection. As demonstrated by previous studies, decrement in visual sensitivity or visual prepulse strength causes a delay in the onset of PPI: a shift of the bell‐shaped curve to the right (Aubert et al ., ; Ces et al ., ). However, no shift in the onset of PPI was detected in KO mice.…”
Section: Discussionmentioning
confidence: 97%
“…The absence of effect on acoustic PPI is somewhat not surprising knowing that D1R rather than D2R plays a prominent role in the modulation of acoustic PPI in mice. Indeed, several research groups, including our, showed that direct stimulation of D1R but not D2R produces disruption of acoustic PPI in mice, a pharmacological profile opposite to that obtained in rats (Ralph‐Williams et al ., ; Ralph & Caine, ; Geyer, ; Ces et al ., ). Our data therefore extend these mouse studies by showing that genetic deletion of GPR88 activity in striatal D2R‐MSNs is ineffective on acoustic PPI.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations